Міжнародна практика заходів, спрямованих на зміцнення довіри між державою та організаціями громадянського суспільства - Лаба, О.; Laba, О. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто міжнародний досвід, спрямований на зміцнення довіри між органами державної влади та організаціями громадянського суспільства. Виділено реалізовані заходи, спрямовані на зміцнення довіри громадян до спроможності органів державної влади забезпечувати належне управління. The article deals with international experience aimed at building confidence between the authorities and civil society organizations. The author points out the following measures to strengthen public confidence in the ability of public authorities to ensure the proper management: the development of a joint statement by civil society and the priorities in the field of management, as well as objectives and mechanisms, the development of minimum standards and / or guidelines for public advice, drafting of projects and signing the institutional arrangements and binding recommendations on the appointment of members of civil society, methods of organization and financing of such pieces of advice, the establishment of the consolidated advisory portal as a central gathering unit for citizens opinions to policy proposals and draft regulations, providing easy access to documents and information by implementing rules unification government web sites, the introduction of legislative regulation of lobbying activities and other successful forms of cooperation.
The International Practice of Measures Aimed at Building Confidence Between the State and Civil Society Organizations.
Keywords: органи державної влади; організації громадянського суспільства; неурядові організації; Європейський Союз; програма розвитку ООН; public authorities; civil society organizations; non-governmental organizations; the European Union; the United Nations Development Programme